MZ BAKERY BREAD PRODUCTION QUALITY CONTROL USING SATISTICAL QUALITY CONTROL - NLP Suciptawati; NW Rita Damayanthi, F Olandha, P Ariesta Candra W, I Komang Satya Dharma (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This research aims to determine the factors that cause damage to bread production at MZ bakery and to find out whether the bread products produced are under control. The results of this research show that the types of damage that occur in bread production are charred, the filling comes out, and the size of the bread is not appropriate. Judging from the Pareto diagram, the most dominant type of defect is that the bread filling comes out in the chocolate banana bread, while the chocolate flavored bread is dominated by burnt bread. From the fishbone chart, it can be seen the factors that cause defects in bread, namely human factors, machines or equipment, methods, raw materials and the environment. The error proportion control chart (P-chart) shows that statistical quality control in bread production at MZ Company is within statistical control limits.